2017
DOI: 10.1071/fp16078
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal behaviour under terminal drought affects post-anthesis water use in wheat

Abstract: Post-anthesis water use is important for grain yield in wheat under drought because this water is immediately used for grain filling. The aim of this study was to determine whether root capacity for water uptake from deeper layers in the soil profile differed between two genotypes with contrasting stomatal behaviour under terminal drought. The wheat cultivar Drysdale and the breeding line IGW-3262 were grown in 1 m deep pots in a glasshouse under well-watered conditions until anthesis, when three watering trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Hence, our results showed that branches of most trees studied could effectively continue to get a continuous water supply by using the cracking method for detachment from the tree prior to gas exchange and photosynthesis measurements. Stomatal conductance (g s ) is another indicator of water, energy and CO 2 cycles between plants and the atmosphere (Roche, 2015; Saradadevi et al., 2016). Plants can vary the size of stomata to adapt to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our results showed that branches of most trees studied could effectively continue to get a continuous water supply by using the cracking method for detachment from the tree prior to gas exchange and photosynthesis measurements. Stomatal conductance (g s ) is another indicator of water, energy and CO 2 cycles between plants and the atmosphere (Roche, 2015; Saradadevi et al., 2016). Plants can vary the size of stomata to adapt to the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The pots (0.15 m diameter and 1.0 m deep) contained 26 kg of soil (volume 0.01766 m3). Several studies have reported that the above volume of soil and particularly depth (1 m) did not show root development restrictions in wheat (Aziz et al, 2016;Saradadevi et al, 2017;Figueroa-Bustos et al, 2019;Pooniya et al, 2019). In addition, Turner (2018) suggested that large tall pots better simulate water extraction and root development similar to field conditions than smaller pots.…”
Section: Plant Materials and Growing Conditionsmentioning
confidence: 99%
“…These traits are aimed at boosting crop yields by increasing harvest index, stem carbohydrate levels, tiller number, plant height, water use and transpiration efficiency, carbon isotope discrimination and root depth (Blum 2005; Collins et al 2008; Salekdeh et al 2009; Fleury et al 2010; Rebetzke et al 2013). Although these traits managed to gradually improve wheat productivity in water-challenged environments (Richards et al 2014), they did not contribute significantly to drought tolerance per se (Condon et al 2004; Blum 2005; Saradadevi et al 2017a, b). There are very few drought-induced tolerance traits in wheat.…”
mentioning
confidence: 99%